AIRWAYS EAR AND MASTOID BONE DISEASES IN ST.-PETERSBURG (ANALYSIS OF 2003-2009 YEARS) - S.M. Kharit; O.V. Iozefovich; T.G. Kokareva; N.P. Akincheva ("Paediatrician" Publishers LLC, 2010)
Analysis of morbidity with airways (including pneumonia), ear and mastoid bone diseases in children in 2003-2009 years was performed on the basis of City Organizational-Methodical Center of Assessment and Prognosis of Mother's and Child's Health, St.-Petersburg. The data was presented in summary documents for children 0-14 years old (form № 12) and for infants (form № 31). Growth of morbidity with airways pathologies and pneumonias during last 7 years, remaining mortality due to pneumonias in hospitals and tendency to its increase in infants, stable quantity of patients with otitis show necessity of inclusion of effective and modern prophylactic measures including vaccination against pneumococcal infections. Key words: children, morbidity, diseases of airways, diseases of ear and mastoid bone.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):24-28)